2021
DOI: 10.1093/qjmed/hcab113.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of very early use of caffeine citrate in preterm neonates needing respiratory support

Abstract: Background Caffeine citrate is one of the most widely used medications in neonatal intensive care units. It is a respiratory stimulant which has well established therapeutic effects in apnea and extubation. Little is known about the very early use of caffeine citrate in preterm neonates. We aim to explore the effectiveness of its very early use in reducing the duration of the respiratory support used and not just extubation. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Early initiation of caffeine therapy can not only reduce the incidence of BPD [ 9 ] but also improve long-term lung function [ 23 ]. A prospective phase 3 clinical trial indicated the early initiation of caffeine has effectively and safely decreased duration of respiratory support used and ICU stay without the development of any complications [ 24 ]. A retrospective study showed that high dose caffeine may provide additional benefit in reducing the risk of bronchopulmonary dysplasia and extubation failure, but may also increase the risk of cerebellar hemorrhage and seizures [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early initiation of caffeine therapy can not only reduce the incidence of BPD [ 9 ] but also improve long-term lung function [ 23 ]. A prospective phase 3 clinical trial indicated the early initiation of caffeine has effectively and safely decreased duration of respiratory support used and ICU stay without the development of any complications [ 24 ]. A retrospective study showed that high dose caffeine may provide additional benefit in reducing the risk of bronchopulmonary dysplasia and extubation failure, but may also increase the risk of cerebellar hemorrhage and seizures [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical trial published in 2021 reported different results. According to this study, caffeine administration at the initiation of mechanical ventilation accelerated extubation without causing complications [ 60 ]. This variation in results is also seen in other cohort studies, and it seems that clinical trials with larger studied populations and longer follow-up times may help determine the optimal use of caffeine.…”
Section: Main Textmentioning
confidence: 99%